2009
DOI: 10.4137/ccrep.s2204
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Due to Clostridium Difficile: Case Report and Review of the Literature

Abstract: Objective: The purpose of this study is to report a case of C. diffi cile bacteremia in a Crohn's disease patient and to review the literature on previously reported cases.Methods: Searches of MEDLINE and PubMed databases were made. Results:We report the fi rst case of C. diffi cile bacteremia in a Crohn's disease patient. There are 15 other reported cases of C. diffi cile bacteremia reported in the literature. We found that the majority of patients (10 of 15 patients) had polymicrobial bacteremia and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Indeed, monomicrobial CDB was present as frequently as CDB associated with additional pathogens to C. difficile (30/60, [50%]), which is similar to the 50% (6/12) of Lee et al series, even if it has been reported that CDB were rather polymicrobial infections probably because of the small number of cases recorded at that time [27], [43], [44], [45]. In CDB, isolates other than C. difficile are often also from the gut flora.…”
Section: Systematic Reviewsupporting
confidence: 70%
“…Indeed, monomicrobial CDB was present as frequently as CDB associated with additional pathogens to C. difficile (30/60, [50%]), which is similar to the 50% (6/12) of Lee et al series, even if it has been reported that CDB were rather polymicrobial infections probably because of the small number of cases recorded at that time [27], [43], [44], [45]. In CDB, isolates other than C. difficile are often also from the gut flora.…”
Section: Systematic Reviewsupporting
confidence: 70%
“…Traditional factors associated with intestinal CDI, including antibiotic exposure, hospitalization, and possibly PPI use, have been described in earlier reports of extraintestinal CDI 11,12,26 and were present in our cohort. Most patients in our cohort had a diagnosis of cancer or IBD, which has been described previously.…”
Section: Discussionmentioning
confidence: 75%
“…Most patients in our cohort had a diagnosis of cancer or IBD, which has been described previously. 10,11,26 They possessed multiple risk factors for intestinal CDI, including frequent hospitalization, antimicrobial exposure, immunocompromised status, and surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressive antibiotic therapy and use of rifampin need to be tailored to individual patients. The literature supports aggressive treatment of C. difficile associated mycotic aneurysms due to the high mortality rate [ 15 ].…”
Section: Discussionmentioning
confidence: 99%